2009
DOI: 10.1248/cpb.57.1267
|View full text |Cite
|
Sign up to set email alerts
|

Structures of New Phenylbutanoids and Nitric Oxide Production Inhibitors from the Rhizomes of Zingiber cassumunar

Abstract: The Zingiberaceae plant, Zingiber cassumunar (Z. cassumunar), is widely distributed in the Southeast Asian countries and was called as "phlai" in Thailand. The rhizomes of this plant are used as a spice and also used for treatment of asthma, bronchitis, gastrointestinal distress, etc., in traditional Thai medicine. Recently, several chemical and biological studies on Z. cassumunar have been reported. [1][2][3][4][5] For example, several phenylbutanoids isolated from Z. cassumunar were reported to possess P-gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…In addition, curcumin, which was found as a minor compound in Z. cassumunar, has an ability to suppress the expression of COX-2 (Surh and Kundu, 2007). Other mechanisms include the inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production, experimented in mouse peritoneal macrophages in which DMPBD, TMPBD, and cassumunaquinone showed IC 50 of 69, 83, and 47 μM, respectively (Nakamura et al, 2009). In addition, Chaiwongsa and co-workers reported an anti-inflammatory activity of compound D against the IL-1 induced catabolic gene expression involved in cartilage degeneration (Chaiwongsa et al, 2013).…”
Section: Chemical Constituents and Anti-inflammatory Activity Of Prasmentioning
confidence: 99%
“…In addition, curcumin, which was found as a minor compound in Z. cassumunar, has an ability to suppress the expression of COX-2 (Surh and Kundu, 2007). Other mechanisms include the inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production, experimented in mouse peritoneal macrophages in which DMPBD, TMPBD, and cassumunaquinone showed IC 50 of 69, 83, and 47 μM, respectively (Nakamura et al, 2009). In addition, Chaiwongsa and co-workers reported an anti-inflammatory activity of compound D against the IL-1 induced catabolic gene expression involved in cartilage degeneration (Chaiwongsa et al, 2013).…”
Section: Chemical Constituents and Anti-inflammatory Activity Of Prasmentioning
confidence: 99%
“…34) As a continuing study, effects of the principal constituents from the rhizomes of Z. cassumunar on the invasion of HT1080 cells through Matrigel-coated filters were examined (Table 3). Among them, phlain I (9) and III (10) (12), and (Ϫ)-b-sesquiphellandrene (22) showed anti-invasion effects. Particularly, 12 significantly inhibited the invasion [inhibition (%) 46.8Ϯ7.2 (pϽ0.05) at 30 mg/ml].…”
Section: Inhibition Of Effects Of Principal Constituents From Z Cassmentioning
confidence: 99%
“…In the course of our studies on bioactive constituents from Zingiberaceae plant, [1][2][3][4][5][6][7][8][9][10][11][12] we previously reported that the methanolic extract from the rhizomes of Zingiber (Z.) cassumunar showed inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in mouse peritoneal macrophages.…”
mentioning
confidence: 99%
See 2 more Smart Citations